Experimental Nuclear Medicine Meets Tumor Biology - Theresa Balber; Loan Tran; Katarína Benčurová; Julia Raitanen; Gerda Egger; Markus Mitterhauser (MDPI AG, 2022)
Personalized treatment of cancer patients demands specific and validated biomarkers for tumor diagnosis and therapy. The development and validation of such require translational preclinical models that recapitulate human diseases as accurately as possible. Moreover, there is a need for convergence of different (pre)clinical disciplines that openly share their knowledge and methodologies. This review sheds light on the differential perception of biomarkers and gives an overview of currently used models in tracer development and approaches for biomarker discovery.